PENGUATAN KESEHATAN MENTAL REMAJA MELALUI PENDEKATAN INTERDISIPLINER DALAM MANAJEMEN PENDIDIKAN ISLAM - Nurul Masruni (CV. ADIBA AISHA AMIRA, 2025)
Adolescent mental health issues are increasingly becoming major concerns at both national and global levels, particularly due to the high prevalence of disorders such as stress, anxiety, and depression that stem from academic pressure, social interactions, technological advancement, and digital culture. This article discusses the importance of an interdisciplinary approach in Islamic education management that integrates psychology, sociology, and Islamic education itself into the development of policies, curricula, and learning strategies. Such an approach is expected to prevent, detect, and address adolescent mental health problems in a holistic and contextual manner. Additionally, the use of digital technology in mental health education has become an important strategy in supporting students’ psychological and spiritual well-being. The implementation of this approach aims to cultivate a young generation that is not only academically competent but also mentally, emotionally, and spiritually resilient. The vital role of Islamic educational management is essential in building an inclusive, adaptive, and sustainable educational ecosystem for adolescent mental well-being amid the challenges of the modern era.